(untitled) (Journal on studies and research of academic knowledge, 2015)
From a chronological and processual approach, this article analyzes the compulsive relocation that was the subject a vast underserved population settled on the shores of the Paraná River and urban streams in the city of Posadas (Argentina). The study also analyzed, as socio-spatial rearrangements through policy interventions/urban renewal and relocation - programs have generated new core areas and correlatively new urban peripheral areas, where are located the housing complexes for families displaced. The segregating effect of relocation refers to the consequences of displacement of a more integrated area to the city center (and the labor market) to a more distant and isolated from the center. Process that affects not only in the loss of the right to urban space and the structure of opportunities, but also in reproductive practices. Constituting this situation as a highly unequal and exclusionary factor.